THE DIFFICULTIES FACED BY EFL GOOD SPEAKING ACHIEVERS AND THE STRATEGIES OF LEARNING SPEAKING IN SOLVING THEIR PROBLEMS - Ulfa Nur Laili; Yahya Alaydrus; Nuse Aliyah Rahmati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
AbstrakThe aim of this research is to describe the speaking difficulties faced by good speaking achievers, and to explain learning strategies used by good speaking achiever of English department of University of Islam Malang overcome their difficulties. Here, good speaking achievers are the forth semester students who can speak English very well in which they get A score in every semester and participated in competition related to English. This study used descriptive qualitative method. The researcher took two selected participants from the fourth grade of University of Islam Malang. The researcher used three instruments; interview guide, document and documentation. The finding of the study explained that mostly good speaking students had difficulties in learning speaking. The problems faced by the learners were lack of vocabulary, difficult in pronunciation, nervousness and less confident. The participants also had some strategies to overcome their problems. To encourage new vocabularies, the strategies that good speaking students used were watching the movie and listening to music. Then, practicing speaking often was strategy that the learner applied to overcome heir difficulties in pronunciation. Moreover, the strategy that participant used in solving their nervousness and their less confidence was talking to the lecturer and their close friends. Key Words: Speaking skill, speaking difficulties, learning strategies.